PENINGKATKAN HASIL BELAJAR BIOLOGI MENGGUNAKAN PETA PIKIRAN (MIND MAPPING) PADA MATERI SISTEM REGULASI KELAS XI IPA.3 SMAN 1 RAMBAH ROKAN HULU TAHUN PELAJARAN 2019/2020 - Evanauli Nasution (JURNAL PENDIDIKAN ROKANIA, 2020)
This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four steps: namely, planning, action, observation, and reflection. The subject of this study was class XI IPA.3 SMA Negeri 1 Rambah with 35 students. To obtain data in this study, researchers used two instruments namely Biology test results from students. Improved learning outcomes can be seen from the number of students who complete the KKM set by the school. The results of data analysis in cycles one and two show that there is an increase in student learning outcomes. The number of students who completed the KKM score increased from 51.43% in the previous UH to 68.57% in the first cycle and 82.86% in the second cycle. In general it can be concluded that the Application of Mind Mapping Learning can improve student learning outcomes